(untitled) (Journal of the College of Basic Education, 2022)
The study included the detection the effect of Surlactin produced by Lactobacillus acidophilus bacteria against Staphylococcus bacteria isolated from different injuries includes wound infections ,burns , wounds,and urinary tract infection . 33 isolates of S.aureus Bacteria and 27 isolates of S.epidermidis bacteria were Dignased in average of (%41.77, %38.18) from 79 isolates for different types of bacteria were collected from injuries and Diagnosed for cultural and microscopic characteristics and Biochemical tests and confermation test using Vitek 2 system. The Resuts of the study confirmed the Activity of Surlactin Crude extract from L.acidophilus superratant in Remoral of Biofilm and inhihition of adherence of S.epidermidis the also may have an effective inhibitor of the growth of bacteria S.aureus after dialysis gainst 0.01 mol of phosphate buffer , and the concentration of protein and Carbohydrates in crude extract extract 3 microgram/ml and 7 microgram/ml Respectirely